Silver nanoparticles in mouthwashes against infection caused by SARS-CoV-2: a scoping review - Molena, Kelly Fernanda; Martins, Camila Raíssa Oliveira Gontijo; Oliveira, Carolina Alves Freiria de; Feres, Murilo Fernando Neuppmann; Queiroz, Alexandra Mussolino de (Brazilian Dental Science, 2023)
The Silver nanoparticle (AgNPs) have received attention for their antiviral potential against SARS-CoV-2. The objective is to conduct a scope review and map the scientific evidence on the use of AgNPs in mouthwashes as an adjunct in decreasing the viral load in the oral cavity of patients with SARS-CoV-2. A search was performed in the PubMed, Medline, Scielo databases, and a manual search in the reference lists, following the standards of the Joanna Briggs Institute for Scoping Review without restriction of year, language or sample size. Thus, 14 articles were included, where they researched the use of AgNPs with antiviral effect against SARS-CoV-2, mouthwashes for SARS-CoV-2 and AgNPs as mouthwashes. We can suggest that AgNPs are likely antiviral therapies for SARS-CoV-2 and its use in mouthwashes associated with other therapies are promising strands for decreasing viral load and infection by the virus.KEYWORDSNanoparticles; Silver; Mouthwashes; COVID-19; SARS-CoV-2.